2020
DOI: 10.30659/e.5.1.43-54
|View full text |Cite
|
Sign up to set email alerts
|

Developing Intercultural Language Learning (ILL) model to teach writing skills at Indonesian private universities

Abstract: This study was aimed at developing an intercultural language learning (ILL) model and finding out its effectiveness to increase students’ writing skills. The kind of this study was procedural research (R&D) design. This study was preceded with the development phases and continued by field-testing. The field-testing was conducted by using a quasi-experimental method to know the effectiveness of the developed learning model. The sample included 64 students. The students were divided into two groups and each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
3
10
0
1
Order By: Relevance
“…The data also revealed that some of the participants were not able to produce a full sentence. It is in line with Haerazi and Irawan (2020b) who state writing skills are uneasy for students who learn English as a foreign language. Based on this result, twenty out of the 106 sentences were not complete sentences.…”
Section: Tasksupporting
confidence: 56%
“…The data also revealed that some of the participants were not able to produce a full sentence. It is in line with Haerazi and Irawan (2020b) who state writing skills are uneasy for students who learn English as a foreign language. Based on this result, twenty out of the 106 sentences were not complete sentences.…”
Section: Tasksupporting
confidence: 56%
“…It means that the students have high motivation to have more activities dealing with the written texts that can be accessed and implemented in their daily communication. It is in line with Haerazi, Prayati, and Vikasari (2019) who state motivation plays an important role to acquire language skills. In addition, students expect to have reading activities motivating themselves which is effected by the techniques in teaching EFL reading (Cahyono & Widiati, 2006;Hadi, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…From Tarigan's opinion, that the ability to write for students is very important, but teaching writing in schools is often not balanced with language teaching, so that writing skills are not optimal. Language skills are usually only emphasized on linguistic knowledge and lack of training so that students' writing results are not good, it can be seen from the many choices of inaccurate words, ineffective sentences, difficulty expressing ideas, difficulty making sentences, and being unable to develop ideas regularly and systematically [5]- [7]. One of the various types of text is complex procedure text.…”
Section: Introductionmentioning
confidence: 99%